Epidural combined optical and electrical stimulation induces high-specificity activation of target muscles in spinal cord injured rats - Guo, Xiao-Jun; Zhao, Ziyi; Chang, Jia-Qi; He, Le-Wei; Su, Wen-Nan; Feng, Ting; Zhao, Can; Xu, Meng; Rao, Jia-Sheng (Frontiers in Neuroscience, 2023)
Introduction: Epidural electrical stimulation (EES) has been shown to improve motor dysfunction after spinal cord injury (SCI) by activating residual locomotor neural networks. However, the This is a provisional file, not the final typeset article stimulation current often spreads excessively, leading to activation of non-target muscles and reducing the accuracy of stimulation regulation.Objectives: Near-infrared nerve stimulation (nINS) was combined with EES to explore its regulatory effect on lower limb muscle activity in spinal-cord-transected rats.Methods: In this study, stimulation electrodes were implanted into the rats' L3-L6 spinal cord segment with T8 cord transected. Firstly, a series of EES parameters (0.2-0.6mA and 20-60Hz) were tested to determine those that specifically regulate the tibialis anterior (TA) and medial gastrocnemius (MG). Subsequently, to determine the effect of combined optical and electrical stimulation, near-infrared laser with a wavelength of 808nm was used to irradiate the L3-L6 spinal cord segment while EES was performed. The amplitude of electromyography (EMG), the specific activation intensity of the target muscle, and the minimum stimulus current intensity to induce joint movement (motor threshold) under a series of optical stimulation parameters (power: 0.0-2.0W; pulse width: 0-10ms) were investigated and analyzed.Results: EES stimulation with 40Hz at the L3 and L6 spinal cord segments specifically activated TA and MG, respectively. High stimulation intensity (>2×motor threshold) activated non-target muscles, while low stimulation frequency (<20Hz) produced intermittent contraction. Compared to electrical stimulation alone (0.577±0.081 mV), the combined stimulation strategy could induce stronger EMG amplitude of MG (1.426±0.365mV) after spinal cord injury (P<0.01). The combined application of nINS effectively decreased the EES-induced motor threshold of MG (from 0.237±0.001mA to 0.166± 0.028mA, P<0.001). Additionally, the pulse width (PW) of nINS had a slight impact on the regulation of muscle activity. The EMG amplitude of MG only increased by ~70% (from 3.978 ± 0.240 mV to 6.753 ± 0.263 mV) when the PW increased by 10fold (from 1ms to 10ms).The study demonstrates the feasibility of epidural combined electrical and optical stimulation for highly specific regulation of muscle activity after SCI, and provides a new strategy for improving motor dysfunction caused by SCI.